2014
DOI: 10.1155/2014/407049
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Organic and Inorganic Amendments Induce Changes in the Mobility of Mercury and Macro- and Micronutrients of Soils

Abstract: Both soil organic matter and sulfur (S) can reduce or even suppress mercury (Hg) mobility and bioavailability in soil. A batch incubation experiment was conducted with a Chernozem and a Luvisol artificially contaminated by 440 mg·kg−1 Hg showing wide differences in their physicochemical properties and available nutrients. The individual treatments were (i) digestate from the anaerobic fermentation of biowaste; (ii) fly ash from wood chip combustion; and (iii) ammonium sulfate, and every treatment was added wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…One of the main reasons for the application of amendments to soils was to increase the pH of the soil and thus reduce the mobility of metal in multi-contaminated soil. Analysis of the chemical composition of the digestate and fly ash revealed high levels of macro-and micronutrients (metal salts, oxides, hydroxides, and carbonates) (García-S anchez et al, 2014). Digestate and fly ash were able to increase the pH of soil reaching values up to 8 as previously has been observed by Garcia-S anchez et al, 2015. In our study, we also detected its ability for increasing the EC of soil treated after 30 and 60 days.…”
Section: Tablesupporting
confidence: 68%
See 1 more Smart Citation
“…One of the main reasons for the application of amendments to soils was to increase the pH of the soil and thus reduce the mobility of metal in multi-contaminated soil. Analysis of the chemical composition of the digestate and fly ash revealed high levels of macro-and micronutrients (metal salts, oxides, hydroxides, and carbonates) (García-S anchez et al, 2014). Digestate and fly ash were able to increase the pH of soil reaching values up to 8 as previously has been observed by Garcia-S anchez et al, 2015. In our study, we also detected its ability for increasing the EC of soil treated after 30 and 60 days.…”
Section: Tablesupporting
confidence: 68%
“…Meanwhile, protease activity did not suffer significant changes as a consequence of the low input of N by the addition of fly ash. However, the increase observed in the activity of o-diphenol oxidase could have been due to: i) dead microbes that contributed to organic carbon enrichment; and ii) organic carbon that was partly constituted by more recalcitrant compounds of phenolic origin (Flaig, 1971;Waldrop and Zack, 2006;Cassuci et al, 2003).…”
Section: Soil Microbial Activities and Physiological Diversitymentioning
confidence: 99%
“…However, in our case, the low input and availability of C substrates provided to soils by fly ash application could be responsible for the dehydrogenase activity found, as previously reported by García-Sánchez et al (2015b). It has been observed that the total S content provided to both soils by fly ash application promoted a low mobility of S portions (Garcia-Sánchez et al 2014). This finding could be associated with the arylsulfatase activity found in both soils, Chernozem and Luvisol non-and Hg-contaminated samples amended with fly ash where no changes were detected (Fig.…”
Section: Soil Enzymes Activitiesmentioning
confidence: 77%
“…Digestate is characterized by high content in inorganic-N forms, such as ammonium as previously described by Alburquerque et al (2012a), which could be responsible for the elevated pH found in these samples. On the other hand, the effectiveness of fly ash application increasing the pH in Hg-contaminated samples and therefore reducing the Hg mobility could be affected predominantly by the soil type (Garcia-Sánchez et al 2014). The low sorption capacity and OM content in Luvisol Hg-contaminated samples amended with fly ash resulted in a pH decrease compared with non-Hg-contaminated samples.…”
Section: Changes Of Chemical Variablesmentioning
confidence: 99%
See 1 more Smart Citation